2014
DOI: 10.1063/1.4866715
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on properties of ultrafast switching in a bulk gallium arsenide avalanche semiconductor switch

Abstract: Articles you may be interested inNon-linear absorption of 1.3-μm wavelength femtosecond laser pulses focused inside semiconductors: Finite difference time domain-two temperature model combined computational study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 30 publications
1
27
0
5
Order By: Relevance
“…A strong electric field leads to intensive impact-ionization within the domain: each domain represents an intensive source of nonequilibrium carriers. In 2014, it was shown that the self-supporting conducting state in photoconductive switches can be explained by the appearance of collapsing domains in electron-hole plasma [24]. The lock-on effect that we have discovered in GaAs pulse-sharpening diodes bears a strong similarity to the lock-on effect in photoconductive switches.…”
Section: Resultsmentioning
confidence: 69%
“…A strong electric field leads to intensive impact-ionization within the domain: each domain represents an intensive source of nonequilibrium carriers. In 2014, it was shown that the self-supporting conducting state in photoconductive switches can be explained by the appearance of collapsing domains in electron-hole plasma [24]. The lock-on effect that we have discovered in GaAs pulse-sharpening diodes bears a strong similarity to the lock-on effect in photoconductive switches.…”
Section: Resultsmentioning
confidence: 69%
“…It's a typical direct semiconductor having band gap of 1.424 eV at 300 K. Due to its high electron mobility (8500 cm 2 /(V·s)), it is used in ultrafast devices [4].…”
Section: Gaasmentioning
confidence: 99%
“…Из литературы известны другие механизмы переключения структур из GaAs в открытое состояние в режиме лавинного пробоя. К ним, например, относится распространение волн ударной ионизации или генерация коллапсирующих доменов Ганна в лавинном режиме [7,8,11,12]. Первый из упомянутых механизмов маловероятен, так как лавинные S-диоды переключаются в условиях развитого лавинного пробоя и при отсутствии значительных перенапряжений.…”
unclassified